Case Report: Complete atrioventricular block and left ventricular outflow tract obstruction as primary manifestations of immunoglobulin G4-related disease - Liu, Yihua; Schnedecker, Lucie; Eggenspieler, Florian; Mandry, Damien; Mohamed, Shirine; Grandmougin, Daniel; Maureira, Juan Pablo (Frontiers in Cardiovascular Medicine, 2025)
BackgroundImmunoglobulin G4-related disease (IgG4-RD) is a systemic immunologic fibroinflammatory condition that can affect a wide range of organ systems. In this study, we present a rare case in which the primary manifestations were complete heart block and left ventricular outflow tract (LVOT) obstruction due to the involvement of the cardiac skeleton.Case presentationA 66-year-old man presented with syncope. An evaluation revealed paroxysmal complete atrioventricular block (AVB) and LVOT obstruction caused by diffuse fibrous thickening of the aortic valve extending to the anterior mitral leaflet, with a maximal gradient of 70 mmHg. A semiurgent operation was performed, including aortic and mitral valve replacement with bioprostheses and implantation of a definitive epicardial pacemaker. A histopathologic examination suggested IgG4-RD; however, glucocorticoid therapy was initially withheld. Two months later, the patient developed recurrent AVB and pacemaker dysfunction. Salvage glucocorticoid therapy led to the normalization of pacemaker thresholds.ConclusionsIgG4-RD may underlie valvulopathy and conduction disorders via lymphoplasmacytic infiltration and fibrosis of the cardiac skeleton. Surgical intervention and timely glucocorticoid therapy are associated with favorable outcomes.